Technological & Intellectual Progress of Indian Knowledge System - Purohit, Vishnudut (Jaipur: ABD Publishers, 2025)
Technological & Intellectual Progress of Indian Knowledge System is a riveting exploration of India's unparalleled contributions to science, technology and intellectual advancement. This book shines a spotlight on the remarkable achievements of ancient Indian thinkers, inventors and scholars whose groundbreaking ideas laid the foundation for modern progress. The book traces the journey of India's ingenuity - from the precision of vedic mathematics to the groundbreaking astronomical calculations of Aryabhata from the architectural marvels of temples to the transformative advancements in metallurgy and medicine. It delves into how ancient texts like the Charaka Samhita and Sushruta Samhita set global benchmarks in healthcare, while innovations like the zero revolutionized mathematics and computation. This work goes beyond chronicling achievements, it deciphers the underlying philosophies that fueled such progress - principles of sustainability, holistic thinking and a relentless pursuit of knowledge system has seamlessly adapted to and shaped global technological and intellectual landscapes. Technological & Intellectual Progress of Indian Knowledge System inspires readers to embrace the timeless brilliance of India's heritage as a blueprint for future breakthroughs.
Keywords: Textiles; Linguistics and Literature -- Indian Literature -- Indian Philosophy; Sanskrit -- Classical Language of Indian Literature; Classical Texts -- Ramayana -- Mahabharata -- Bhagavadgita; Prakrit and Pali; Tamil Sangam Literature; Arts and Aesthetics